The search for stability through stabilisation: case studies from Afghanistan and Nepal - Dennys, C (Cranfield University, 2013)
This thesis focuses on what stability is, and what interventions have supported stability in four communities in Afghanistan and Nepal. It is the author’s view that this is the first in-depth village level assessment of how populations conceive of stability and stabilisation and thus presents a challenge to existing analysis and research about how to foster stability in contexts in extreme tension and often violent conflict. The thesis argues that international, particularly Western, notions of stability and stabilisation processes have failed to grasp the importance of local political legitimacy formation, which is a vital aspect of contemporary statebuilding of a ‘non-Westphalian’ nature. The interventions, across defence, diplomatic and defence lines, have also at times undermined one another and in some cases contributed to instability. This is particularly acute when the interventions have been motivated by the conflicting demands of statebuilding, counter-insurgency (COIN) and development theories. The thesis argues that the nature of the interventions, their conception of stability and exogenously-driven goals limit the ability to promote stability. Research findings indicate that that local processes of stabilisation have, at times, proven to be more enduring but only in circumstances where a combination of local and national political processes have allowed political legitimacy to be formed and maintained. Research findings also suggest that the more successful stability interventions have been critically supported by humanitarian and security activities which have provided for the immediate needs of the population. Longer term stability has only been embedded in contexts which have also been able to exploit economic opportunities.
© Cranfield University
Keywords: Intervention; Stabilisation; Statebuilding